Analisis Literasi Matematis Pada Pembelajaran Statistika Siswa Kelas IX di MTs Al – Asyirotussafiiyyah - Apriati, Adinda Nisa; Budiman, Indra (Prosiding Sesiomadika, 2024)
This study aims to analyze the mathematical literacy of junior high school students in the context of learning statistics in grade IX. There were seventeen grade IX students who participated in this research, which was carried out at MTs Al-Asyirotussafiiyyah. This research uses qualitative techniques with descriptive methodology. Assessment of mathematical literacy in the form of description problems with statistical material is used in data collection strategies. Indicators of mathematical literacy ability tests used in this study include, 1) Understanding data, 2) Interpreting data, and 3) Communicating data. Data collection is obtained by using test instruments to obtain results of students' abilities in mathematical literacy, and non-test instruments in the form of interviews to find out more deeply how students can literate well. The results showed that the mathematical literacy ability of grade IX students at MTs Al-Asyirotussafiiyyah was still relatively low. Of the 17 students there are 4 students at level 1, 12 students are at level 2 and 1 student is at level 3. No students are able to reach level 4 – level 6